2021
DOI: 10.1109/jeds.2021.3095389
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Electrical Charging Speed Limit of ReRAM Devices

Abstract: Redox-based random-access memory (ReRAM) has the potential to successfully address the technological barriers that today's memory technologies face. One of its promising features is its fast switching speed down to 50 ps. Identifying the limiting process of the switching speed is, however, difficult. At sub-nanosecond timescales three candidates are being discussed: An intrinsic limitation, being the migration of mobile donor ions, e.g. oxygen vacancies, the heating time, and its electrical charging time. Usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…Recently, we have shown that 50 ps fast SET times can be achieved for TaO x - and ZrO x -based VCM devices, which corresponds to the limitation of the experimental setup. We also demonstrated that the SET kinetics are mainly delayed by the electrical charging time in the subnanosecond regime and not by intrinsic processes, such as the migration of ions or the heating of the filamentary region . The fast heating results from the narrow filament, which has only a diameter in the range from 1 nm to 3 nm .…”
Section: Introductionmentioning
confidence: 80%
“…Recently, we have shown that 50 ps fast SET times can be achieved for TaO x - and ZrO x -based VCM devices, which corresponds to the limitation of the experimental setup. We also demonstrated that the SET kinetics are mainly delayed by the electrical charging time in the subnanosecond regime and not by intrinsic processes, such as the migration of ions or the heating of the filamentary region . The fast heating results from the narrow filament, which has only a diameter in the range from 1 nm to 3 nm .…”
Section: Introductionmentioning
confidence: 80%
“…Recently, we have shown that 50 ps fast SET times can be achieved for TaO x -and ZrO x -based VCM devices [39], which corresponds to the limitation of the experimental setup. We also demonstrated that the SET kinetics are mainly delayed by the electrical charging time in the sub-nanosecond regime and not by intrinsic processes, such as the migration of ions or the heating of the filamentary region [40]. The fast heating results from the narrow filament, which has only a diameter in the range from 1 nm to 3 nm [41].…”
Section: Introductionmentioning
confidence: 79%
“…At the center the inner conductor is tapered to 2 µm, matching the dimensions of the 2 × 2 µm 2 devices. More information and illustrations of this structures are given in [40].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations